The Tools of Owatatsumi: Japan's Ocean Surveillance and Coastal Defence Capabilities - Ball, Desmond (ANU Press, 2015)
Japan is quintessentially by geography a maritime country. Maritime surveillance capabilities - underwater, shore-based and airborne - are critical to its national defence posture. This book describes and assesses these capabilities, with particular respect to the underwater segment, about which there is little strategic analysis in publicly available literature.